Induction of apoptosis in 9-nitrocamptothecin-treated DU145 human prostate carcinoma cells correlates with de Novo synthesis of CD95 and CD95 ligand and down-regulation of c-FLIPshort - Chatterjee, Devasis; Krammer, Peter H.; Peter, Marcus E. (Cancer research, 2001)
Stimulation of CD95 leads to oligomerization of this receptor and the recruitment of the Fas-associated death domain (FADD) and procaspase-8 to form the death-inducing signaling complex (DISC). Subsequent proteolytic activation of caspase-8 at the DISC leads to the activation of downstream caspases and execution of apoptosis. The anticancer drug 9-nitrocamptothecin (9NC) inhibits the nuclear enzyme topoisomerase I (Top1), an event followed by apoptosis of cancer cells. We investigated whether other mechanisms downstream of the DNA-Top1-9NC complexing step regulate the apoptotic ability of 9NC in DU145 cells. We demonstrate that induction of apoptosis in DU145 cells, upon exposure to 9NC, is associated with de novo expression of CD95 and CD95L, suggesting that 9NC-induced apoptosis is mediated by the CD95 system. In this line, we observed early activation of procaspase-3, -7, and -8, but not -1, -9, and -10. Moreover, 9NC treatment resulted in the dramatic down-regulation of c-FLIPshort expression, but not that of c-FLIPlong or FADD. Furthermore, incubation of DU145 cells with a neutralizing antibody (NOK-1) to CD95L or transient transfection of a c-FLIPshort expression vector into DU145 cells partially abrogated 9NC-triggered apoptosis. We propose that 9NC triggers apoptosis by driving DU145 cells from a nonapoptotic status (c-FLIPshorthigh, CD95low, CD95Llow) toward a proapoptotic status (c-FLIPshortlow, CD95high, CD95Lhigh). These findings indicate that in addition to a Top1-mediated effect, 9NC can additionally activate a CD95/CD95L-dependent apoptotic pathway.
Gesehen am 28.04.2021
Im Titel ist der Ausdruck "short" tiefgestellt